2006
DOI: 10.1002/biot.200600032
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the membrane‐bound glucose oxidation system in Gluconobacter oxydans significantly increases gluconate and 5‐keto‐D‐gluconic acid accumulation

Abstract: Gluconobacter oxydans DSM 2343 (ATCC 621H)catalyzes the oxidation of glucose to gluconic acid and subsequently to 5-keto-D-gluconic acid (5-KGA), a precursor of the industrially important L-(+)-tartaric acid. To further increase 5-KGA production in G. oxydans, the mutant strain MF1 was used. In this strain the membrane-bound gluconate-2-dehydrogenase activity, responsible for formation of the undesired by-product 2-keto-D-gluconic acid, is disrupted. Therefore, high amounts of 5-KGA accumulate in the culture m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…5c). Similar effects had been observed previously in Gluconobacter oxydans MF1 when the gene coding for glucose dehydrogenase or gluconate-5-dehydrogenase was overexpressed (Merfort et al 2006).…”
Section: Enzyme Activitysupporting
confidence: 86%
“…5c). Similar effects had been observed previously in Gluconobacter oxydans MF1 when the gene coding for glucose dehydrogenase or gluconate-5-dehydrogenase was overexpressed (Merfort et al 2006).…”
Section: Enzyme Activitysupporting
confidence: 86%
“…For industrial production of 5KGA, many attempts at improvement of 5KGA production have been done using genetically modified strains. [8][9][10][11] In our previous study, 92% conversion from D-glucose and D-gluconate to 5KGA was achieved in G-GA medium, 7) and in this study 5KGA was produced at an 87% conversion rate from D-glucose as sole substance using a wild-type Gluconobacter strain. Thus Gluconobacter without gene modification can be useful for high 5KGA conversion from D-glucose by a culture with controlled medium pH.…”
mentioning
confidence: 58%
“…In this study however we found a previously described strain of G. oxydans (B58) to be more effective at leaching REE than the isolates. Further evaluation of G. oxydans for REE recovery applications is warranted; in addition to the robust leaching performance observed in this study, G. oxydans is also an attractive candidate for metabolic modeling and genetic engineering due to the availability of an annotated genome sequence (Prust et al, 2005) and developed genetic systems (Herrmann et al, 2004;Merfort et al, 2006;Prust et al, 2005;Schleyer et al, 2008;Zhang et al, 2010), as well as a recent developed metabolic network model (Wu et al, 2014). Genetic modifications and or manipulation of cultivation conditions to increase acid production and achieve even higher REE recovery will be considered.…”
Section: Discussionmentioning
confidence: 97%